(untitled) (Research, Society and Development, 2020)
The Brazilian Government lack of capacity to provide basic public services led to the need to employ the concession mechanism as provided by law, where the granting authority sets the maximum tariff to be charged for services and controls and inspects their quality from a set of predefined parameters to be inspected as mentioned in the concession contract. The objective of the present work is to present a useful procedure for the Public Administration to evaluate basic services in a concession system based on information obtained from users. It is a theoretical-empirical work which includes a bibliographic research, the pertinent legislation, and a field research, where semi-structured questionnaires were applied to the direct and to indirect users of urban public transport system by bus. Confirming the analyzed theoretical framework, the opinion of users establishes as a reliable source to assess the quality of services, being an excelent instrument for inspecting public services concessions.